Analisis Potensi Penerimaan Pajak Reklame Kota Bandung Periode Tahun 2001 - 2007 - Aristanti Widyaningsih (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2009)
The research is purposed to know the potential of advertisement tax income in Bandung. The research method, descriptive analytical method with calculate the level of region autonomy with collecting financial report 2001 up to 2007 in official bandung region income.The results of the research shows that the potential of the advertisement tax from 2001 up to 2002 under target and realization of advertisement tax income. Whereas, the potential of the advertisement tax from 2003 up to 2007 higher from target and realization of advertisement tax income.The writer also wants to give the recommendation to increase collecting subject andobject af advertisement tax so that the potention and the realization advertisement tax income can be known.